PENJERNIHAN MINYAK PELUMAS BEKAS DENGAN METODE PENJERAPAN SUATU USAHA PEMANFAATAN KEMBALI MINYAK PELUMAS BEKAS SEBAGAI BASE OIL - Johanna Lianna; Yunia Karyati; Herry Santosa (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Used lubricating oil which is fantastic in number is potential to be recycled into base oil to remove contaminants that contained in the lubricating oil. Research carried out is intended to determine the most effective type of adsorbent between coal, activated carbon or silica gel; assess the influence of concentration alkilbenzenesulfonate; as well as the most effective purification media between bentonite and zeolite as an effort in order to purify used lubricating oils. The study was conducted in three stages. First, the preparatory phase consisting of (a) characterization of lubricating oil, (b) reducing the size of various types of adsorbent to obtain the size of 2 to 3.25 mm, (c) activation of silica gel and zeolite, (d) making alkilbenzenesulfonate solution (ABS) on various concentrations. Second, the adsorption step to remove contaminants, for example solid material, metal, and water. The experiments were performed on the type of adsorbent : coal, activated carbon and silica gel. Third, purification stage using the alkilbenzenesulfonate as solvent. The experiments were performed by using solution of alkilbenzenesulfonate at various concentrations as well as purification media such as zeolite and bentonite. At the end of the experiment, tested the results against the percent transmittance, viscosity, viscosity index, and specific gravity. Ttransmittance was tested by using a spectrophotometer with a specification SP-300 OPTIMA at wavelength 680 nm, the viscosity was tested using viskosimeter Ostwald, viscosity index is calculated by comparing the viscosity experimental results with the viscosity of water, while the specific grafity is calculated by comparing the density experimental results with the density of water. To produce refined products that approach the specification of base oil, adsorption process is better done using coal as adsorbent, purification process using pure ABS and the use of zeolite as a medium for purification.